Profil Organ Pencernaan, Kualitas Karkas dan Potongan Bagian Karkas Ayam Broiler yang Diberi Tepung Daun Mengkudu (Morinda Citrifolia Linn) Fermentasi Sebagai Imbuhan Pakan - Auza, Fuji Astuty; Badaruddin, Rusli; Isnaeni, Purnaning Dhian; Kimestri, Asma Bio (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2023)
This study aims to examine the effect of using fermented noni leaf flour and determine the appropriate level to support the productivity of broiler chickens. This study used one hundred DOC broiler chickens with feed consisting of corn, concentrate, bran, and fermented noni leaf meal. The study was arranged using a completely randomized design (CRD) consisting of 4 noni leaf level treatments: P0: 0% fermented noni leaf powder, P1 = 5%, P2 = 10%, and P3 = 15%. The parameters observed were the weight and relative length of the digestive organs, the weight and percentage of the carcass, the weight and percentage of abdominal fat, and the percentage of carcass pieces. The results showed that the use of fermented noni leaf flour up to 15% in the ration had a significant effect (P>0.05) on the percentage of small intestine weight (duodenum, jejenum and ileum), cecum length, carcass weight, abdominal fat, thigh carcass pieces, and wing. However, it did not affect (P>0.05) the weight of the ventricular, proventriculus, cecum, large intestine, length of the small intestine and large intestine, and breast and back carcass pieces. Using fermented noni leaf flour up to 15% can increase the percentage of small intestine weight, caecum length, carcass weight, abdominal fat, carcass wing, and thigh pieces in broiler chickens aged 35 days.